Potassium Sources and Rates for Drip Irrigated Polyethylene Mulched Chilli Pepper - Hamdani, Kiki Kusyaeri; Susila, Anas Dinurrohman; Purwono, Purwono; Suketi, Ketty (Journal of Tropical Crop Science, 2019)
Fertigation with drip irrigation is one of the technologies to solve fertilization and irrigation problems in chilli pepper production using polyethylene mulch. Potassium (K) is one of the important macro nutrients that affect plant growth and development due to its roles in the biochemical and the biophysical processes in plants. The objective of this study was to determine the best sources and the optimum rates of potassium for drip irrigated polyethylene mulched chilli pepper field production. The study was conducted in January until July 2018 at Tajur Experimental Farm, Center for Tropical Horticulture Study, Bogor Agricultural University. The experimental design was a split plot with the K sources (KCl, ZK, NPK) as main plots and K rates that consisted of five levels (0, 68, 136, 204, 272 kg K2O. ha-1) as sub-plots. The results showed that the best optimum rate of K to produce fruit is 101.11 kg K2O.ha-1 with a maximum yield of 2.26 t.ha-1. Chilli crops fertilized with NPK and KCl had the greatest fruit weight per plant, fruit weight per plot, and fruit weight per hectare.